2016
DOI: 10.1038/srep26739
|View full text |Cite
|
Sign up to set email alerts
|

A novel species of torque teno mini virus (TTMV) in gingival tissue from chronic periodontitis patients

Abstract: A new species of torque teno mini virus, named TTMV-222, was detected in gingival tissue from periodontitis patients using a viral metagenomics method. The 2803-nucleotide genome of TTMV-222 is closely related to TTMV1-CBD279, with 62.6% overall nucleotide similarity. Genetic analyses of the new virus genome revealed a classic genomic organization but a weak identity with known sequences. The prevalence of TTMV-222 in the periodontitis group (n = 150) was significantly higher than that in the healthy group (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…We also describe in this paper viruses that have been previously associated with hepatitis such as TTV-1, 11, 16 and SEN virus H [ 14 , 41 ]; other viruses have been recently described in serum samples from HIV patients (P19-3, P13-4, P9-6, P1-3); yet other sets were described in patients with various conditions, including lymphocytic leukaemia (TTV 10) [ 42 ], gingival periodontitis (TTMV 18) [ 43 ], haemophilia (TTMDV MDJN47 and MDJN97) [ 44 ] and in pregnant women whose offspring developed leukaemia and lymphomas (TTV S45, S57, S66, S69, S72, S80 and S97) [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also describe in this paper viruses that have been previously associated with hepatitis such as TTV-1, 11, 16 and SEN virus H [ 14 , 41 ]; other viruses have been recently described in serum samples from HIV patients (P19-3, P13-4, P9-6, P1-3); yet other sets were described in patients with various conditions, including lymphocytic leukaemia (TTV 10) [ 42 ], gingival periodontitis (TTMV 18) [ 43 ], haemophilia (TTMDV MDJN47 and MDJN97) [ 44 ] and in pregnant women whose offspring developed leukaemia and lymphomas (TTV S45, S57, S66, S69, S72, S80 and S97) [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al . reported that a new virus (TTMV-222) may be associated with inflammation in chronic periodontitis patients using viral metagenomics [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been detected in various types of carcinoma including leukemia and colorectal cancer. However, the pathogenicity of TTV at present is unclear [7,18,20,26,27]. Due to the lack of available tissue-culture methods, TTV infection is often diagnosed on the basis of TTV-DNA detection by PCR.…”
Section: Introductionmentioning
confidence: 99%
“…Based on its genome structure, it was later renamed torque teno virus (Latin torques, i.e., "necklace", and tenuis, i.e., "thin"). TTV is presently classified in the family Anelloviridae [6,7], which also contains other small emerging infectious agents like torque teno mini virus [8] and torque teno midi virus [9]. All of these viruses exhibit a high prevalence, a global distribution, and a high genetic variability [10,11].…”
Section: Introductionmentioning
confidence: 99%